Customer Attractiveness of Medical Service Robots in the Indian Healthcare Industry - Anuja Agarwal, Deepika Dixit, Vijay Shankar, Rakhiben Vijaykumar Shah, Kanishka Vashishta, Kajal Srivastava (European Economic Letters (EEL), 2024)
This paper explored the potential of medical robots in the Indian healthcare sector by understanding the attractiveness of medical robots to patients. The current state of the Indian healthcare sector has been discussed, including the shortage of medical personnel and the need for improved access to medical services. An extensive literature review was followed by data collection from Indian patients using online and offline survey methods. Exploratory factor analysis was conducted to analyze the data. Based on the results, a framework has been proposed constituting three factors: service alignment, automation support, and patient engagement, which contribute to the attractiveness of medical robots among patients, the successful implementation, and usage of medical robots. The service providers can use this framework to understand what the patients look for and what is the best they can provide them. However, challenges like cost and technological limitations must be handled well for successful integration.